Conocimiento ecológico local sobre ecosistemas marinos en dos comunidades costeras : El Valle y Sapzurro (2012)
ABSTRACT: The inhabitants of the Colombian coastal populations of El Valle, in the Pacific, and Sapzurro, in the Caribbean Darien, have ecological knowledge about coastal ecosystems that is a result of their constant relation with the sea, through fishing and navigation. The sea is a source of food and economical resources, but it is also the sphere where the male personality is forged. The accurate knowledge about mangrove, coral, coral reef, beaches and fishing grounds has been enriched through the dialog between local inhabitants and researchers in the conservation biology field. However, the tensions with researchers and environmental authorities still exist. The paper suggests that local ecological knowledge studies could be a starting point for maintaining a more horizontal dialogue between environmentalist and the populations with livelihoods derived of fishing.